Risk factors for injury in Olympic-style competition taekwondo: a systematic review - Lystad, R. P.; Swain, M. S.; Graham, P. L. (The Journal of Sports Medicine and Physical Fitness, 2013)
Aim: The aim of this review was to systematically collate and qualitatively evaluate the epidemiologic data on risk factors related to injuries in taekwondo athletes. Methods: Electronic searches of relevant literature were carried out in the AusportMed, CINAHL, PubMed, Scopus, and SPORTDiscus databases. A study was included if: 1) it was a prospective experimental or observational investigation; 2) it contained data on Olympic-style taekwondo athletes; and 3) it contained data on risk factors for injuries. All eligible studies were assessed by two independent reviewers. Results: Sixteen studies were deemed eligible for inclusion, of which a total of nine unique data sets were identified. Six potential risk factors were found to have been prospectively investigated to date, of which only three were shown to be associated with the occurrence of injury. The available data indicated that competing in heavier weight divisions was associated with increased overall injury incidence rates. In addition, adolescent athletes and athletes lacking blocking skills were both found to be associated with increased occurrence of concussion injuries. Conclusion: There is a paucity of identified risk factors for injury in taekwondo. Future epidemiologic research should consider a wider range of potential risk factors, in particular modifiable risk factors, and translate ascertained factors into practical preventive efforts.